2016
DOI: 10.1016/j.cmet.2016.05.004
|View full text |Cite|
|
Sign up to set email alerts
|

Osteocalcin Signaling in Myofibers Is Necessary and Sufficient for Optimum Adaptation to Exercise

Abstract: Summary Circulating levels of undercarboxylated and bioactive osteocalcin double during aerobic exercise at the time those of insulin decrease. In contrast, circulating levels of osteocalcin plummet early during adulthood in mice, monkeys and humans of both genders. Exploring these observations revealed that osteocalcin signaling in myofibers is necessary for adaptation to exercise by favoring uptake and catabolism of glucose and fatty acids, the main nutrients of myofibers. Osteocalcin signaling in myofibers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
418
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 347 publications
(456 citation statements)
references
References 47 publications
11
418
0
11
Order By: Relevance
“…Sclerostin is secreted by mature osteocytes, inhibiting the Wnt signalling pathway that leads to decreased bone formation and increased muscle differentiation 66. Osteocalcin is a hormone produced by osteoblasts that reduces sensitivity to insulin and enhances the exercise capacity 67, 68. FGF23 induces hypertrophy at least on cardiac muscle, although its effects on skeletal muscle are not fully understood 69.…”
Section: Vitamin D Physiologymentioning
confidence: 99%
“…Sclerostin is secreted by mature osteocytes, inhibiting the Wnt signalling pathway that leads to decreased bone formation and increased muscle differentiation 66. Osteocalcin is a hormone produced by osteoblasts that reduces sensitivity to insulin and enhances the exercise capacity 67, 68. FGF23 induces hypertrophy at least on cardiac muscle, although its effects on skeletal muscle are not fully understood 69.…”
Section: Vitamin D Physiologymentioning
confidence: 99%
“…Accordingly, when fed a normal diet, Ocn-deficient mice (Ocn -/-) exhibit reduced glucose tolerance, insulin sensitivity, and circulating insulin levels, as well as decreased energy expenditure and increased fat mass (2). Mechanistic studies conducted in cell cultures and mice showed that OCN improves glucose handling by promoting insulin secretion from β cells (3,4), by favoring glucose uptake in myofibers (5), and by increasing energy expenditure (6). Studies in mice demonstrated that OCN function in β cells and myofibers is mediated through its binding to the G protein-coupled receptor family C group 6 member A (GPRC6A) (3,5).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistic studies conducted in cell cultures and mice showed that OCN improves glucose handling by promoting insulin secretion from β cells (3,4), by favoring glucose uptake in myofibers (5), and by increasing energy expenditure (6). Studies in mice demonstrated that OCN function in β cells and myofibers is mediated through its binding to the G protein-coupled receptor family C group 6 member A (GPRC6A) (3,5). This pathway appears to be conserved in humans, since human OCN can bind and activate human GPR-C6A (7), while mutations or polymorphisms in human GPRC6A are associated with insulin resistance (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…They also showed that exogenous osteocalcin can dramatically restore the exercise capacity of old mice to that of 3 months old mice. 28 Since no significant difference exists between the osteocalcin content of Dmp1-Cre Mbtps1 cKO mice and controls at 12 months of age (23.4 ± 7.1 vs 30.8 ± 11.6 ng ml À 1 , respectively; (Gorski, JP, unpublished result) and osteocalcin did not stimulate muscle growth and regeneration, 28 we do not believe osteocalcin has a prominent role in the Mbtps1 cKO muscle phenotype ( Figure 1). …”
mentioning
confidence: 99%
“…26 Although age was once presumed to cause dramatic reductions in optimal muscle performance after endurance training, further research has shown that the rate of decline may be much slower than once believed. 27 Recently, Karsenty and colleagues 28 showed that osteocalcin signaling in myofibers is necessary for maximal adaption to exercise. They also showed that exogenous osteocalcin can dramatically restore the exercise capacity of old mice to that of 3 months old mice.…”
mentioning
confidence: 99%